Divergence in Qibla Direction Determination: A Fiqh-Based Analysis and Its Societal Implementation - Nizam, Ahmad; SA, Romli; Yazwardi, Yazwardi (Universitas Islam Negeri Raden Fatah Palembang, 2025)
This study explores the social reality surrounding discrepancies in Qibla direction among mosques in Palembang City, which, based on astronomical and scientific assessments, have proven to be inaccurate. The research aims to analyze community responses to these directional inconsistencies and to propose solutions that integrate modern technology and astronomical science into religious practice in a more thoughtful and contextually sensitive manner. Employing a sociological framework rooted in ethnographic and cultural anthropological approaches, the study collected data through Qibla recalibration observations, in-depth interviews, and literature review. The findings were analyzed using a descriptive qualitative method, complemented by astronomical and scientific perspectives. The results reveal that the misalignment of Qibla direction in many mosques largely stems from reliance on approximate traditional methods (taqribi), shaped by local wisdom, and from limited understanding of precise astronomical calculations and digital calibration tools. Nevertheless, the community exhibits a socially harmonious and religiously tolerant stance, prioritizing Islamic brotherhood (ukhuwah Islamiyah) over strict alignment with the Shafi'i school’s doctrinal precision. As a constructive step forward, this study suggests the need for community-based astronomical education and hands-on training in Qibla calibration applications. Such efforts can help improve directional accuracy while preserving social cohesion and preventing potential conflicts within religious communities.